2005
DOI: 10.1177/0306624x04269003
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Multiple Drug Misuse and Crime

Abstract: Research that has investigated the association between specific drug types and crime has tended to focus on the specific drug type in isolation from other drugs. The main problem with this is that it cannot be assumed that the association between specific drug use and crime will be the same regardless of the additional drugs consumed. The research aimed to investigate whether there was a correlation between number and type of drugs used and involvement in crime. The analysis of multiple drug use was based on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 16 publications
3
41
1
3
Order By: Relevance
“…It has been reported that various pharmaceutical combinations may cause higher levels of violence due to their chemical nature (14). In this study, in the presence of confounding variables drug abusers with the lowest level of education had higher chances of committing crimes than drug abusers with higher levels of education.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…It has been reported that various pharmaceutical combinations may cause higher levels of violence due to their chemical nature (14). In this study, in the presence of confounding variables drug abusers with the lowest level of education had higher chances of committing crimes than drug abusers with higher levels of education.…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, concomitant addiction to both narcotics and alcohol did not increase the chance of criminal activity. On the other hand, some studies (14,15) reported that the probability of criminal activity is higher in the case of multiple drug use. Chaiken et al (24) also reported that the rate of criminal activity in multiple drug users in the USA was 10 -20 times higher than the rest of drug abusers (15).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although studies to date have confirmed a strong relationship between criminal conduct and substance abuse (Bennett & Holloway, 2005;Coid, Carvell, Kittler, Healey, & Henderson, 2000;Felson & Staff, 2010;Menard, Mihalic & Huizinga, 2001;Roca & Caixal, 1999;Sanford & Arrigo, 2005;Santamaría & Chait, 2004), the causal direction of the relationship has not been identified (Boles & Miotto, 2003;Kuhns & Clodfelter, 2009). Addiction can lead to criminal behaviour because many addicts commit crimes to finance their habits and avoid withdrawal symptoms (Bennett & Holloway, 2005).…”
Section: Criminological Profile Of Patients In Addiction Treatmentmentioning
confidence: 99%